Strategic Foresight dalam Manajemen Pendidikan untuk Membangun Sekolah Masa Depan: Systematic Literature Review - Trian Hermawan; Tarekah Hasanah; Wahyu Febriana; Binti Luthfiyah; Nirva Diana; Aan Komariah; Badrudin (WISE Pendidikan Indonesia, 2026)
Global uncertainty driven by digital disruption, artificial intelligence, ecological risk, social polarization, and shifting skills demand requires schools to move beyond routine annual planning toward anticipatory and future-oriented management. This systematic literature review synthesizes studies on strategic foresight in educational management for building future-ready schools. The review covers publications from 2015 to 2025 and adapts PRISMA 2020 and PRISMA-S principles. Searches were conducted across Scopus, Web of Science Core Collection, ERIC, Google Scholar, and complementary policy sources from OECD and UNESCO. From 1,240 initial records, 286 duplicates and 24 non-target records were removed before screening. After title-abstract screening, full-text eligibility assessment, and quality appraisal, 42 documents were included in the qualitative thematic synthesis. The findings show that strategic foresight in educational management is constructed as an anticipatory capacity rather than a linear prediction mechanism. Key practices include horizon scanning, weak signal analysis, scenario planning, strategy stress-testing, future visioning, professional learning, and adaptive governance. The publication trend indicates two major waves: a foundational phase in 2015 and a policy consolidation phase in 2025. The review proposes the FORESIGHT-SCHOOL model as a conceptual framework for integrating foresight into school planning, implementation, evaluation, and organizational learning. The study contributes to strategic educational management by positioning foresight as a core capability for building adaptive, resilient, and future-ready schools.